A gibberellin methyltransferase modulates the timing of floral transition at the Arabidopsis shoot meristem. Issue 4 (16th June 2020) - Lee, Joanne E.; Goretti, Daniela; Neumann, Manuela; Schmid, Markus; You, Yuan
Abstract : The transition from vegetative to reproductive growth is a key event in the plant life cycle. Plants therefore use a variety of environmental and endogenous signals to determine the optimal time for flowering to ensure reproductive success. These signals are integrated at the shoot apical meristem (SAM), which subsequently undergoes a shift in identity and begins producing flowers rather than leaves, while still maintaining pluripotency and meristematic function. Gibberellic acid (GA), an important hormone associated with cell growth and differentiation, has been shown to promote flowering in many plant species including Arabidopsis thaliana, but the details of how spatial and temporal regulation of GAs in the SAM contribute to floral transition are poorly understood. In this study, we show that the gene GIBBERELLIC ACID METHYLTRANSFERASE 2 ( GAMT2 ), which encodes a GA‐inactivating enzyme, is significantly upregulated at the SAM during floral transition and contributes to the regulation of flowering time. Loss of GAMT2 function leads to early flowering, whereas transgenic misexpression of GAMT2 in specific regions around the SAM delays flowering. We also found that GAMT2 expression is independent of the key floral regulator LEAFY but is strongly increased by the application of exogenous GA. Our results indicate that GAMT2 is a repressor of flowering that may act as a buffer of GA levels at the SAM to help prevent premature flowering.